US School Attack Findings Show Need for Reform, Accountability (Human Rights Watch, 2026)
Reported findings that the United States is responsible for the recent deadly school attack in Iran, and that it was based on outdated targeting data, highlight the need for reform and accountability within the US military to minimize civilian harm during conflict.
Iran